2009
DOI: 10.1002/anie.200900063
|View full text |Cite
|
Sign up to set email alerts
|

A Supramolecular Approach for Preparation of Size‐Controlled Nanoparticles

Abstract: A supramolecular approach has been developed for the preparation of supramolecular nanoparticles (SNPs) with variable sizes (30-450 nm) from three different molecular building blocks using a cyclodextrin/adamantane recognition system. Positron emission tomography (PET) was employed to study the biodistribution and lymph node drainage of the SNPs in mice. The sizes of the SNPs affect their in vivo characteristics (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(146 citation statements)
references
References 34 publications
3
141
0
2
Order By: Relevance
“…Although most clinically approved anticancer nanomedicines have the sizes ranging from 100 to 200 nm, 10 11 it was recently found that NPs smaller than 100 nm exhibited enhanced antitumoral performance in vivo with a better tissue penetration. 12 For instance, Nishiyama et al studied sub-100 nm polymeric micelles with diameters of 30, 50, 70 and 100 nm in both highly and poorly permeable tumors. 13 They found that all the polymer micelles could penetrate highly permeable tumors, but the 30 nm micelle are the only one could penetrate poorly permeable pancreatic tumors to achieve an antitumor effect.…”
Section: Introductionmentioning
confidence: 99%
“…Although most clinically approved anticancer nanomedicines have the sizes ranging from 100 to 200 nm, 10 11 it was recently found that NPs smaller than 100 nm exhibited enhanced antitumoral performance in vivo with a better tissue penetration. 12 For instance, Nishiyama et al studied sub-100 nm polymeric micelles with diameters of 30, 50, 70 and 100 nm in both highly and poorly permeable tumors. 13 They found that all the polymer micelles could penetrate highly permeable tumors, but the 30 nm micelle are the only one could penetrate poorly permeable pancreatic tumors to achieve an antitumor effect.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we introduce a new gene delivery system that centers around the use of two functional components with nanoscale features, including 1) DNA⊂SNPs: supramolecular nanoparticle (SNP) vectors 3743 for encapsulation of plasmid DNA, and 2) Ad-SiNWS: adamantane (Ad)-grafted silicon nanowire substrates 44,45 that can mediate the transduction of DNA⊂SNPs from surrounding solution/medium into cells that settle on Ad-SiNWS. Figure 1a illustrates the working mechanism of this NanoSubstrate-Mediated Delivery (NSMD) platform for both in vitro and in vivo settings: multivalent molecular recognition between the Ad motifs on Ad-SiNWS and the CD motifs on the surfaces of DNA⊂SNPs leads to dynamic assembly and local enrichment of DNA⊂SNPs from the surrounding solution/medium onto Ad-SiNWS.…”
Section: Introductionmentioning
confidence: 99%
“…36 This self-assembled synthetic strategy enables control over the sizes, surface chemistry, and payloads of SNP vectors for a wide range of diagnostic and therapeutic applications, such as positron emission tomography (PET) imaging, 37 magnetic resonance imaging (MRI), 43 photothermal treatment, 39 on-demand release of a drugs, 43 as well as highly efficient delivery of genes, 40,48,49 transcription factors, 50 and drug-polymer conjugates. 42 As for DNA-encapsulated SNPs (DNA⊂SNPs), Figure 1b illustrates the mechanism of the supramolecular synthetic strategy, 3743 CD-PEI and Ad-PAMAM first self-assemble, via the cooperation of Ad/CD recognition motifs, into cationic hydrogel networks that can encapsulate DNA plasmids, thus creating the cores of SNPs. 39,40 The ligand module (Ad-PEG) then acts as a capping/solvation reagent that constrains continuous growth of the DNA-encapsulated hydrogel networks and simultaneously confers desired solubility, structural stability, and stealth (in circulatory system) to the resulting DNA⊂SNPs with controllable sizes of ca.…”
Section: Introductionmentioning
confidence: 99%
“…41 The activity of a nanoparticle in a biological environment depends on its size, surface chemistry (functionalization at the periphery), charge and shape. 42 Researchers aim to use molecular recognition to create an easy and flexible toolbox to control the properties of these nanoparticles, and to employ the non-covalent nature of the interaction to control the assembly and disassembly properties, and thereby the uptake and release of cargo.…”
Section: Supramolecular Nanoparticles 22mentioning
confidence: 99%
“…In the realm of supramolecular chemistry, on the other hand, the formation of supramolecular nanoparticles (SNPs) 41,42 is controlled by multivalent/monovalent competition between the building blocks. Variation of the stoichiometry of these building blocks is a simple and effective means to tune the size of SNPs in a controllable manner as well as their surface chemistry.…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 99%